1999
DOI: 10.1017/s1355838299981669
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of 23S ribosomal RNA requires the exoribonuclease RNase T

Abstract: Ribosomal RNAs are generally synthesized as long, primary transcripts that must be extensively processed to generate the mature, functional species. In Escherichia coli, it is known that the initial 30S precursor is cleaved during its synthesis by the endonuclease RNase III to generate precursors to the 16S, 23S, and 5S rRNAs. However, despite extensive study, the processes by which these intermediate products are converted to their mature forms are poorly understood. In this article, we describe the maturatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 28 publications
(38 reference statements)
8
88
0
2
Order By: Relevance
“…5B) complementary to residues 35-55 of mature 23S rRNA (Charollais et al 2003). Using this probe, we find that wild-type 70S and 50S particles contain mature rRNA and a +1 species, as has previously been reported (Li et al 1999;Charollais et al 2003). In the DrluDłkan mutant, 70S, 62S, and 50S particles also contain predominantly the mature and the +1 species.…”
Section: Further Characterization Of the Drludłkan Mutant Ribosomessupporting
confidence: 77%
“…5B) complementary to residues 35-55 of mature 23S rRNA (Charollais et al 2003). Using this probe, we find that wild-type 70S and 50S particles contain mature rRNA and a +1 species, as has previously been reported (Li et al 1999;Charollais et al 2003). In the DrluDłkan mutant, 70S, 62S, and 50S particles also contain predominantly the mature and the +1 species.…”
Section: Further Characterization Of the Drludłkan Mutant Ribosomessupporting
confidence: 77%
“…Based on these experiments, the apparently full-length 23S and 16S RNA molecules carried normal 5Ј termini (data not shown). To examine the 3Ј termini, chimeric oligonucleotide-directed RNase H cleavage was used (19). These analyses indicated that both the 23S and 16S rRNA species in the double mutant at 42°C have normal 3Ј termini as well (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…This technique can be used to examine the end of large RNA molecules at single nucleotide resolution. Analysis was carried out as described (19). The reaction products were resolved on a 6% polyacrylamide-8.3 M urea gel and analyzed by Northern hybridization.…”
Section: Methodsmentioning
confidence: 99%
“…This includes 16S (this work), 23S (12,17), and 5S (18) rRNAs, tRNAs (9), and other small stable RNAs (19). In all cases, removal of the last precursor residues involves the action of an exoribonuclease.…”
Section: Discussionmentioning
confidence: 99%
“…MG1655 I Ϫ was used as the RNase PH Ϫ strain into which RNase R, RNase II, and PNPase mutations were introduced as described previously (10). Site-directed RNase H Cleavage-Total RNA was isolated using a hot phenol method (11) and subjected to RNase H assay followed by Northern blot analysis (5,12). The chimera C16S3 (5Ј-CCdCdGdAdAGGUUAAGCUACCU-3Ј) was used for 3Ј end cleavage of 16S rRNA, and cleavage products were visualized by using a probe complementary to residues 1502-1523.…”
Section: Bacterial Strains-e Coli Mg1655*(seq) Imentioning
confidence: 99%